War Horse - Morpurgo, Michael; Adapted by Stafford, Nick, 1959- (Oxford, New York Oxford University Press, 2009)
Set during the First World War, this award-winning adaptation of Michael Morpurgo's novel tells the moving story of the bond between a soldier and his horse.
Include Illustration
Keywords: War horses -- World War (1914-1918) -- Drama--Study and teaching (Secondary)